2011
DOI: 10.1128/mcb.05804-11
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of rRNA Methylation for 80S Ribosome Assembly on a Cohort of Cellular Internal Ribosome Entry Sites

Abstract: Protein syntheses mediated by cellular and viral internal ribosome entry sites (IRESs) are believed to have many features in common. Distinct mechanisms for ribosome recruitment and preinitiation complex assembly between the two processes have not been identified thus far. Here we show that the methylation status of rRNA differentially influenced the mechanism of 80S complex formation on IRES elements from the cellular sodiumcoupled neutral amino acid transporter 2 (SNAT2) versus the hepatitis C virus mRNA. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 60 publications
4
62
1
Order By: Relevance
“…6). The importance of L13a for rRNA methylation in the 90S preribosome is consistent with our previous finding that L13a is a component of the fibrillarin-containing C/D box snoRNP complex responsible for methyltransferase activity (15). Another demonstrated function of L13a occurs outside the ribosome.…”
Section: Figsupporting
confidence: 77%
See 2 more Smart Citations
“…6). The importance of L13a for rRNA methylation in the 90S preribosome is consistent with our previous finding that L13a is a component of the fibrillarin-containing C/D box snoRNP complex responsible for methyltransferase activity (15). Another demonstrated function of L13a occurs outside the ribosome.…”
Section: Figsupporting
confidence: 77%
“…In contrast to many other ribosomal proteins of both the small and large ribosomal subunits (48-54), L13a does not affect ribosome biogenesis and maturation or global protein synthesis (14). We have, however, previously demonstrated that L13a is required for rRNA methylation, one of the rRNA modifications that takes place during ribosome biogenesis (15). Here, we confirm that L13a is required for rRNA methylation and demonstrate that this occurs within the 90S preribosome (Fig.…”
Section: Figsupporting
confidence: 74%
See 1 more Smart Citation
“…It would be interesting to assess whether rRNA pseudouridylation regulates, at the translational level, the expression of mRNAs containing a PRF signal, perhaps in a cell-and/or tissue-specific manner. An emerging role for rRNA modifications in regulating specific modes of translation has recently been highlighted by findings that methylation of rRNA is also implicated in IRES-dependent translation of specific cellular mRNAs Belin et al 2009;Basu et al 2011). Furthermore, loss of rRNA methylation at specific sites in zebrafish leads to severe developmental defects (HigaNakamine et al 2012).…”
Section: The Cancerous Translation Machinery Initiation Factors (Eifs)mentioning
confidence: 99%
“…The importance of rRNA modifications is also supported by the finding that rRNA methylation is important for IRES-dependent translation of specific mRNAs. 132,133 The more general model proposed by Ruggero 17 , therefore, is that altered ribosomes can induce tumorigenesis because of specific changes in the translation pattern.…”
Section: Ribosomes and Cancermentioning
confidence: 99%